Corrosion protective poly(o-toluldine) coatings on copper - Shinde, V.; Sainkar, S. R.; Patil, P. P. (Corrosion Science, 2005)
This study examines the use of poly(o-toulidine) (POT) coatings for corrosion protection of copper (Cu) in an aqueous solution of 3% NaCl. The POT coatings were synthesized on Cu substrates under cyclic voltammetric conditions from an aqueous solution of sodium oxalate. The resulting, POT coatings were uniform, shiny and strongly adherent to the Cu substrates. These coatings were characterized by cyclic voltammetry (CV), UV-visible absorption spectroscopy, Fourier transform infrared (FTIR) spectroscopy and scanning electron microscopy (SEM). The ability of POT to serve as a corrosion protective coating for Cu was examined by potentiodynamic polarization measurements and CV. The results of this study clearly reveal that the POT acts as corrosion protective coating on Cu and reduces the corrosion rate of Cu almost by a factor of 40. (c) 2004 Elsevier Ltd. All rights reserved.
Keywords: Conducting polymer coatings; Copper; Corrosion resistant coatings; cyclic voltammetry; poly(o-toluidine) coatings

Pyrazole-tethered heteroditopic ligands and their transition metal complexes: synthesis, structure, and reactivity - Mukherjee, Anuradha; Subramanyam, U.; Puranik, Vedavati G.; Mohandas, T. P.; Sarkar, A. (European Journal of Inorganic Chemistry, 2005)
Various pyrazole-based PN (2a-c) and N,N (3a-b) ligands have been synthesized. Using representative ligands, Ni-II, Co-II, Cu-II, and Cu-I complexes have been prepared and structurally characterized by crystallography. During complexation of Co-II and Cu-II salts, the phosphane part of the PN ligand oxidized to phosphane oxide. For N,N donor ligands, a dimeric chloro-bridged Ni-III complex was obtained. Ni-II complex 4 is an active catalyst for ethylene oligomerization. ((c) Wiley-VCH Verlag GmbH & Co. KGaA, 69451 Weinheirn, Germany, 2005).
Keywords: cobalt; Copper; hemilabile ligands; Nickel; oligomerization; Pyrazole

Formation of poly(o-anisidine) coatings on copper from aqueous salicylate solution - Chaudhari, Sudeshna; Mandale, A. B.; Patil, K. R.; Sainkar, S. R.; Patil, P. P. (Surface & Coatings Technology, 2006)
Poly(o-anisidine) coatings have been electrosynthesized by using cyclic voltammetry on copper from an aqueous salicylate medium. Cyclic voltammetry, UV-visible absorption spectroscopy, Fourier transform infrared spectroscopy, scanning electron microscopy and X-ray photoelectron spectroscopy were used to characterize these coatings, which indicates that the aqueous salicylate solution is a suitable medium for the electrochemical polymerization of o-anisidine on copper substrate. Cyclic voltammetry accompanied by the X-ray photoelectron spectroscopy was used to characterize the surface modifications induced by polarizing the copper substrate in the aqueous salicylate solution (without monomer). It was shown that the polarization of the copper in the aqueous salicylate medium results into the passivation of its surface via the formation of Cu(2)O and/or copper salicylate complex. It was found that the electrochemical polymerization of o-anisidine takes place after the passivation of the copper substrate via fort-nation of Cu(2)O and/or copper salicylate complex and results into the formation of shiny, uniform and strongly adherent poly(o-anisidine). The optical absorption spectroscopy reveals the formation of emraldine salt form of poly(o-anisidine). This study offers an electrochemical polymerization recipe to synthesize strongly adherent poly(o-anisidine) coating on copper from aqueous media for possible use in corrosion protection application. (c) 2005 Elsevier B.V. All rights reserved.
Keywords: conducting polymers; Copper; corrosion protective coatings; cyclic voltammetry; poly(o-anisidine) coatings

Poly(o-toluidine) coatings on copper: electrochemical synthesis from aqueous media - Shinde, V.; Mandale, A. B.; Patil, K. R.; Gaikwad, A. B.; Patil, P. P. (Surface & Coating Technology, 2006)
Poly(o-toluidine) (POT) coatings were synthesized on copper (Cu) by electrochemical polymerization of o-toluidine using aqueous sodium oxalate solution as supporting electrolyte. The resulting coatings were uniform, compact and strongly adherent to the Cu substrate. These coatings were characterized by using cyclic voltammetry, UV-visible absorption spectroscopy, Fourier transform infrared (FTIR) spectroscopy, scanning electron microscopy (SEM), X-ray diffraction (XRD) measurements and X-ray photoelectron spectroscopy (XPS). The results of these studies reveal that the sodium oxalate is suitable supporting electrolyte for the electrochemical polymerization of o-toluidine on Cu substrate. It is found that the electrochemical polymerization of o-toluidine takes place after the passivation of the Cu substrate via formation of copper oxalate (CuC2O4, H2O) layer, which is confirmed by XRD and XPS. The optical absorption spectroscopy study reveals the exclusive formation of the pernigraniline base (PB) form of POT. (c) 2005 Elsevier B.V. All rights reserved.
Keywords: Conducting polymer coatings; Copper; Corrosion resistant coatings; cyclic voltammetry; poly(o-toluidine) coatings

Synthesis and characterization of corrosion protective poly(2,5-dimethylaniline) coatings on copper - Shinde, Vandana; Gaikwad, A. B.; Patil, P. P. (Applied Surface Science, 2006)
Poly(2,5-dimethylaniline) coatings were synthesized on copper (Cu) by electrochemical polymerization of 2,5-dimethylaniline in aqueous salicylate solution by using cyclic voltammetry. The characterization of these coatings was carried out by cyclic voltammetry, UV-visible absorption spectroscopy, Fourier transform infrared (FTIR) spectroscopy and scanning electron microscopy (SEM). The results of these characterizations indicate that the aqueous salicylate solution is a suitable medium for the electrochemical polymerization of 2,5-dimethylaniline to generate strongly adherent and smooth poly (2,5-dimethylaniline) coatings on Cu substrates. The performance of poly(2,5-dimethylaniline) as protective coating against corrosion of Cu in aqueous 3% NaCl was assessed by the potentiodynamic polarization technique. The results of the potentiodynamic polarization demonstrate that the poly(2,5-dimethylaniline) coating has ability to protect the Cu against corrosion. The corrosion potential was about 0.078 V versus SCE more positive in aqueous 3% NaCl for the poly(2,5-dimethylaniline) coated Cu than that of uncoated Cu and reduces the corrosion rate of Cu almost by a factor of 31. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: 5-dimethylaniline) coatings; conducting polymers; Copper; Corrosion resistant coatings; cyclic voltammetry; Electrochemical polymerization; Poly(2

Corrosion protection aspects of electrochemically synthesized poly(o-anisidine-co-o-toluidine) coatings on copper - Pawar, Pritee; Gaikwad, A. B.; Patil, P. P. (Electrochimica Acta, 2007)
The poly(o-anisidine-co-o-toluidine) coatings were synthesized on copper substrates by electrochemical copolymerization of o-anisidine with o-toluidine using sodium salicylate as supporting electrolyte. These coatings were characterized by cyclic voltammetry, UV-vis absorption spectroscopy, Fourier transform infrared spectroscopy (FTIR), nuclear magnetic resonance spectroscopy (NMR) and scanning electron microscopy (SEM). The formation of the copolymer with the mixture of monomers in the aqueous sodium salicylate solution was ascertained by a critical comparison of the results obtained with the polymerization of the individual monomers, o-anisidine and o-toluidine, respectively. The corrosion protection aspects of poly(o-anisidine-co-o-toluidine) coatings to copper was investigated in aqueous 3% NaCl solution by potentiodynamic polarization technique and electrochemical impedance spectroscopy (EIS). The results of the potentiodynamic polarization measurements and EIS studies showed that the poly(o-anisidine-co-o-toluidine) coatings provided the effective corrosion protection to copper than that of respective homopolymers. The corrosion rate is observed to depend on the feed ratio of o-toluidine used for the synthesis of the copolymer coatings. (C) 2007 Elsevier Ltd. All rights reserved.
Keywords: copolymer coatings; Copper; Corrosion resistant coatings; cyclic voltammetry; poly(o-anisidine-co-o-toluidine)

Cu(OTf)(2) catalyzed Biginelli type condensation of aldehydes, beta-keto esters and carbamates: synthesis of 3,4-dihydro[1,3]oxazin-2-ones - Jagdale, Arun R.; Paraskar, Abhimanyu S.; Sudalai, Arumugam (Indian Journal of Chemistry Section B-Organic Chemistry including Medicinal Chemistry, 2008)
Cu(OTf)(2) catalyzes effectively a new multicomponent reaction comprising aldehydes, beta-ketoester and methy carbamate in acetonitrile to afford substituted 3,4-dihydro[1,3]oxazin-2-ones in 60-82% yields. These compounds have been found to show inhibition activity against HL-60 cancer cell.
Keywords: aldehydes; Catalysts; Copper; Multicomponent reaction

Synthesis and corrosion protection study of poly(o-ethylaniline) coatings on copper - Shinde, Vandana; Gaikwad, A. B.; Patil, P. P. (Surface & Coatings Technology, 2008)
Poly(o-ethylaniline) coatings were synthesized on copper (Cu) by electrochemical polymerization of o-ethylaniline in an aqueous salicylate solution by using cyclic voltammetry. The characterization of these coatings was carried out by cyclic voltammetry, UV-visible absorption spectroscopy, Fourier transform infrared spectroscopy (FTIR) and scanning electron microscopy (SEM). The results of these characterizations indicate that the aqueous salicylate solution is a suitable medium for the electrochemical polymerization of o-ethylaniline to generate strongly adherent and smooth poly(o-ethylaniline) coatings on Cu substrates. The performance of poly(o-ethylaniline) as protective coating against corrosion of Cu in aqueous 3% NaCl was assessed by the potentiodynamic polarization technique and electrochemical impedance spectroscopy (EIS). The results of these studies demonstrate that the poly(o-ethylaniline) coating has ability to protect the Cu against corrosion. The corrosion potential was about 0.078 V versus SCE more positive in aqueous 3% NaCl for the poly(o-ethylanitine) coated Cu (similar to 15 mu m thick) than that of uncoated Cu and reduces the corrosion rate of Cu almost by a factor of 70. (C) 2007 Elsevier B.V. All rights reserved.
Keywords: conducting polymers; Copper; Corrosion resistant coatings; cyclic voltammetry; Electrochemical polymerization; poly(o-ethylaniline) coatings

Copper-based catalysts for water gas shift reaction: influence of support on their catalytic activity - Pradhan, S.; Reddy, A. Satyanarayana; Devi, R. N.; Chilukuri, Satyanarayana V. (Catalysis Today, 2009)
Three copper containing catalysts supported on ceria and mixed oxides of ceria with zirconia and titania were prepared by co-precipitation method and their catalytic activity was tested for water gas shift (WGS) reaction. High surface area (>100m(2)/g) mixed oxides were obtained following the present method of preparation. The catalysts were characterized by XRD, H(2)-temperature programmed reduction (TPR), UV-vis and XPS. Catalytic activity was evaluated for water gas shift reaction in the 200-400 degrees C temperature range, The gas hourly space velocity was varied from 5000 to 25,000h(-1) for better evaluation and comparison of their performance. The effect of CO(2) in the feed gas mixture on the WGS activity of these catalysts was also studied. Among the three catalysts studied, CuO-CeO(2)-ZrO(2) mixed oxide shows better activity, implying the influence of support. Characterization of the catalysts after WGS reaction was also carried out in order to investigate structure-property correlation. (c) 2008 Elsevier B.V. All rights reserved.
Keywords: ceria; Ceria-titania; Ceria-zirconia; Co-precipitation; Copper; Water gas shift

Novel electroless process for copper coating of flyash using titania/ultraviolet-radiation/metal catalyst-system - Shijitha, T.; Baiju, K. V.; Shukla, S.; Patil, K.; Warrier, K. G. K. (Applied Surface Science, 2009)
A novel electroless process has been demonstrated in this investigation to coat the surface of flyash particles with a conducting metal such as copper. The conventional electroless process has been modified for this purpose by replacing the tin-palladium catalyst-system with the titania/ultraviolet-radiation/metal catalyst-system, where the metal is either copper or silver as demonstrated here. The mechanism of copper coating of flyash particles in an electroless bath, using the novel methods of surface-sensitization and surface-activation, has been systematically studied by monitoring changes in the surface-morphology, surface-chemistry, and surface-structure of flyash particles using the scanning electron microscope, energy dispersive analysis of X-rays, X-ray photoelectron spectroscope, and X-ray diffraction. It has been revealed that the novel electroless method involves coating the flyash particles with titania photocatalyst via sol-gel, which acts as a surface-sensitizer under the ultraviolet-radiation exposure for the subsequent surface-activation with the copper- or silver-clusters. The latter in turn acts as surface-catalyst for the subsequent Cu-coating in an electroless bath. The proposed mechanism of surface-sensitization and surface-activation of flyash particles using the novel catalyst-system has been compared with that using the conventional catalyst-system. (C) 2009 Elsevier B. V. All rights reserved.
Keywords: Copper; Electroless; Flyash; Photocatalysis; sol-gel; titania

Heterogenized copper catalysts for the amination of arylhalide: synthesis, characterization and catalytic applications - Patil, Nandkumar M.; Gupte, Sunil P.; Chaudhari, Raghunath V. (Applied Catalysis A-General, 2010)
This research investigated the synthesis, characterization and catalytic activity of heterogenized copper complexes for the selective amination of aryl halides. Amination reactions using homogeneous copper catalyst systems are not generally selective and it is also difficult to recover the catalyst from the homogeneous system for recycling. To overcome these difficulties, our efforts were directed towards the development of cheaper heterogeneous catalyst systems, which can be easily recovered and recycled. Heterogenized analogs of the homogenous Cu complexes were prepared using two methods: (a) encapsulation of copper complexes in zeolite-Y and (b) tethering of copper complexes on various supports like zeolite-Y, silica, charcoal, or clay. The encapsulated and tethered copper catalysts on zeolite-Y were characterized using EPR, Diffused reflectance UV-vis, XRD, IAS, ICPES, SEM, and TEM. The results confirmed that the copper complexes were truly heterogenized in zeolite-Y support. Encapsulated and tethered copper complexes were tested for amination of aryl iodide. The effects of various reaction parameters were examined using tethered Cu(Phen)(PPh(3))Br-PTA-Y catalyst to determine optimum conditions. A recycle study of encapsulated and tethered Cu catalyst was carried out to test their robustness for possible commercial exploitation. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: Amination; C-N coupling; Copper; heterogeneous catalysis; mesoporous materials

Chromatographic separations of zinc, iron and copper metal ions through cellulose poroussolid fiber supported solid membrane in mixedsolvent systems - Gaikwad, Abaji G. (Chemical Engineering Communications, 2011)
An interesting aspect of chromatographic separation of zinc, iron, and copper metal ions through a cellulose porous solid fiber supported solid membrane from source solution to receiving phase has been explored in mixed solvent systems. The cellulose porous solid fiber supported solid membrane was prepared by chemically immobilizing tartaric acid. The experimental variables explored were concentration of copper, zinc, and iron metal ions, hydrochloric acid, composition of mixed solvents, and stirring speed. The efficiency of a cellulose porous solid fiber supported solid membrane system has been evaluated for the separation of metal ions. The pre-concentration of metal ions was carried out from the dilute solutions. The two-channel chromatographic cellulose porous solid fiber supported solid membrane system has been investigated for the transport of metal ions from the source solution to receiving phase. The capillary action phenomenon in the cellulose micro fibers plays a significant and active role in the transport of ions through the cellulose porous solid fiber supported solid membrane in mixed solvents.
Keywords: and iron ions: Single- and double-channel membrane system; Cellulose porous solid fiber supported solid membrane; Copper; zinc

Click chemistry: 1,2,3-triazoles as pharmacophores - Agalave, Sandip G.; Maujan, Suleman R.; Pore, Vandana S. (Chemistry-an Asian Journal, 2011)
The copper(I)-catalyzed 1,2,3-triazole-forming reaction between azides and terminal alkynes has become the gold standard of `click chemistry' due to its reliability, specificity, and biocompatibility. Applications of click chemistry are increasingly found in all aspects of drug discovery; they range from lead finding through combinatorial chemistry and target-templated in vitro chemistry, to proteomics and DNA research by using bioconjugation reactions. The triazole products are more than just passive linkers; they readily associate with biological targets, through hydrogen-bonding and dipole interactions. The present review will focus mainly on the recent literature for applications of this reaction in the field of medicinal chemistry, in particular on use of the 1,2,3-triazole moiety as pharmacophore.
Keywords: Click chemistry; Copper; Cycloaddition; pharmacophores; triazoles

Synthesis of Cu-ZnO and C-ZnO nanoneedle arrays on zinc foil by low temperature oxidation route: effect of buffer layers on growth, optical and field emission properties - Jamali-Sheini, Farid; Patil, K. R.; Joag, Dilip S.; More, Mahendra A. (Applied Surface Science, 2011)
Different densities of ZnO nanoneedle films have been prepared by pre-coated zinc foils with thin layer of copper and carbon followed by thermal oxidation at 400 degrees C in air. The X-ray diffraction patterns show well defined peaks, which could be indexed to the wurtzite hexagonal phase of ZnO. The scanning electron microscope images clearly reveal formation of ZnO needles on the entire substrate surface. The X-ray photoelectron spectroscopy studies indicate that Cu and C ions are incorporated into the ZnO lattice. Photoluminescence studies evaluate different emission bands originated from different defect mechanism. From the field emission studies, the threshold field, required to draw emission current density of similar to 100 mu A/cm(2), is observed to be 2.25 V/mu m and 1.57 V/mu m for annealed zinc foil pre-coated with copper and carbon, respectively. The annealed film with copper layer exhibits good emission current stability at the pre-set value of similar to 100 mu A over a duration of 4 h. The results show that buffer layer is an important factor to control the growth rate, resulting in different density of ZnO needles, which leads to field emission properties. This method may have potential in fabrication of electron sources for high current density applications. (C) 2011 Elsevier B. V. All rights reserved.
Keywords: Buffer layer; Carbon; Copper; field emission; Nanoneedle; ZnO

Clay entrapped Cu(OH)(x) as an efficient heterogeneous catalyst for ipso-hydroxylation of arylboronic acids - Dar, Bashir Ahmad; Bhatti, Prince; Singh, A. P.; Lazar, Anish; Sharma, Parduman R.; Sharma, Meena; Singh, Baldev (Applied Catalysis A-General, 2013)
A remarkably active, selective and stable montmorilonite-KSF entrapped Cu(OH)(x) catalyst, has been prepared for the ipso-hydroxylation of arylboronic acids under ambient conditions without requirement of any ligand or base. This catalyst shows excellent reusability without leaching and any significant loss in catalytic activity. The catalyst was characterized using, XRD, SEM, TPR, IR, XPS and BET surface area measurement techniques. (C) 2013 Elsevier B.V. All rights reserved.
Keywords: clay; Copper; heterogeneous catalysis; Phenols; Water chemistry

POM-catalyzed in situ ligand synthesis for the construction of metal complexes and their use in the formation of coordination polymers - Dey, Chandan; Banerjee, Rahul (Chemphyschem, 2013)
Six organicinorganic hybrid materials were synthesized by the in situ oxidation of neocuproine by using MoO3/Na2MoO4 as the catalyst in the presence of Cu(NO3)2. The crystal structures of Mo8-Cu4-PHEN and Mo8-Cu2-5(2PIC) are composed of [Mo8O26]4 polyoxometalate (POM) units, whereas the crystal structure of Mo6-Cu-COPHEN is composed of a [Mo6O19]2 POM unit; both POM units could be considered as the active form of the catalyst. Reaction of the hybrid materials with 1,3,5-benzenetricarboxylic acid (BTC) resulted in the formation of two different coordination polymers (CPs) under different reaction conditions. These CPs, depending on their structural attributes, exhibit distinct differences in the adsorption of H2, CO2, and water. The use of 2-methylpyridine instead of neocuproine does not give any oxidation products under the same reaction conditions due to the incorrect positioning of the methyl group with respect to the CuII center.
Keywords: coordination polymers; Copper; N ligands; organicinorganic hybrid composites; polyoxometalates

Proton-conducting supramolecular metallogels from the lowest molecular weight assembler ligand: a quote for simplicity - Saha, Subhadeep; Schoen, Eva-Maria; Cativiela, Carlos; Diaz, David Diaz; Banerjee, Rahul (Chemistry-A European Journal, 2013)
Oxalic acid has been proven to be the lowest molecular weight organic ligand able to form robust supramolecular metallogel networks in the presence of metal salts. In particular, two novel multifunctional metallogels were readily prepared at room temperature by simple mixing of stock solutions of Cu-II acetate monohydrate or Cu-II perchlorate hexahydrate and oxalic acid dihydrate. Formation of different polymorphs and unprecedented proton conduction under anhydrous conditions were also demonstrated with some of these materials.
Keywords: Copper; low-molecular-weight ligands; metallogels; proton conductivity; supramolecular chemistry

Clay encapsulated Cu(OH)(x) promoted homocoupling of arylboronic acids: an efficient and eco-friendly protocol - Dar, Bashir Ahmad; Singh, Snehil; Pandey, Nalini; Singh, A. P.; Sharma, Priti; Lazar, Anish; Sharma, Meena; Vishwakarma, Ram A.; Singh, Baldev (Applied Catalysis A-General, 2014)
Cu(OH)(x) has been encapsulated over montmorillonite-KSF by simple ologomeric deposition strategy. The resulting catalyst has been employed for selective homocoupling of arylboronic acids under ambient conditions without requirement of any ligand or base. This catalyst is easy to recover and shows excellent reusability without losing its activity. Techniques like XRD, SEM, TPR, IR, BET surface area measurement and XPS were used to characterize the catalyst. The present method promises for the simple and clean homocoupling of arylboronic acids. (C) 2013 Elsevier B.V. All rights reserved.
Keywords: Biaryls; clay; Copper; Heterogenous catalyst; Homocoupling

Effect of composition and pretreatment parameters on activity and stability of Cu-Al catalysts for water-gas shift reaction - Mane, Rasika B.; Jeong, Dae-Woon; Malawadkar, Atul V.; Roh, Hyun-Seog; Rode, Chandrashekhar V. (ChemCatChem, 2014)
We investigated various Cu species responsible for highly efficient Cu-Al oxide catalyst for the water-gas shift reaction (WGSR). The formation of various Cu species was achieved by systematically varying the Cu-Al composition in the coprecipitated mixed Cu-Al oxides. The Cu-Al composition of 70:30 (Cu-Al-7) was the best for WGSR using the reformate gas composition. In addition, the Cu-Al-7 catalyst reduced under 100% H-2, was relatively stable with time on stream of 100 h, at higher gas hourly space velocity of 36201 h(-1). The structural investigation of our coprecipitated catalysts with varying Cu-Al compositions revealed the formation of nonzero oxidation state copper and metallic Cu to be essential for the observed WGSR activity. In addition, the highest activity and stability of Cu-Al-7 catalysts reduced under 100% H-2 at lower temperature was attributed to particle-size stabilization and a lower extent of Cu aggregation by Cu2O and boehmite phases, respectively, along with the formation of various Cu species during the activation protocol for 12 h. Complete CO2 selectivity without methanation was observed for all the Cu-Al compositions irrespective of their pretreatment conditions.
Keywords: aluminum; Copper; fuel cells; Hydrogen; reduction

Bicinchoninic acid-based colorimetric chemosensor for detection of low concentrations of cyanide - Biradar, Archana A.; Biradar, Ankush V.; Sun, Tiffany; Chan, Yung; Huang, Xiaoxi; Asefa, Tewodros (Sensors and Actuators B-Chemical, 2016)
Bicinchoninic acid (BCA) is reagent that is widely used to determine the concentration of proteins in solutions through the colored complex it forms with Cu(I) and the proteins. In this report, we present a new use for BCA, where a highly sensitive method for detection of cyanide ions in solutions by using Cu2+-BCA complex as the chemosensing agent is demonstrated. The detection of cyanide ions is achieved by taking advantage of the nucleophilic attack of the Cu2+-BCA complex by cyanide ions. Upon the addition of cyanide ions, the Cu2+-BCA complex undergoes transformations to free BCA via a series of equilibriums and, as a result, forms different Cu(II)-(BCA)(x)(CN)(y) species depending on the concentrations of cyanide ions in the solution. These different Cu(II)-(BCA)(x)(CN)(y) species, in turn, give different metal-to-ligand charge transfer electronic spectra and colors that are easily detectable both with naked eyes and UV-vis spectroscopy. As the cyanide ion concentration increases, the color of the solution containing the complexes changes from green to purple, red, yellow, and finally colorless, giving a corresponding blue shift in the absorption maxima on their UV-vis spectra. Through this process, the complexes enable detection of cyanide ions with a detection level of up to 0.06 ppm in solutions. Thus, this colorimetric technique based on Cu2+-BCA can make low concentrations of cyanide detectable, well before the concentrations possibly reach lethal amounts. Furthermore, the method is shown to give fast detection response with no interference from other anionic and cationic species and has the potential to be adopted for accurate and convenient analysis of cyanide ions in drinking water sources as well as industrial effluents. (C) 2015 Elsevier B.V. All rights reserved.
Keywords: BCA; Bicinchoninic acid; Chemosensor; Colorimetric sensor; Copper; Cyanide

Study the effect of impact angle on slurry erosion wear of four different ductile materials - Nandre, Bhushan D.; Desale, Girish R. (Materials Today: Proceedings, 2018)
The test rig fabricated for the present work has an ability to study the effect of orientation angle of erosion wear. The particles of Indian Standard sand (Quartz) selected as erodent for the present investigation because it is the most widely occurs in natural slurries. Experimental investigations on erosion behavior of ductile materials AISI SS304, AA 6063, Copper and Brass have been carried out using solid-water mixtures of the above erodent. The erosion wear due to solid-liquid mixture of IS Sand and tap water at different impact angles shows typical ductile erosion behavior for the selected materials. The maximum erosion is observed at 22.5° angle for AISI SS 304, 45o for AA 6063, 22.5o for Copper and 30o for Brass. The minimum erosion is observed at 90o orientation angle for all the materials. The eroded specimens were examined under the Scanning Electron Microscope (SEM) at minimum and maximum wear orientation angles. The SEM micrographs of eroded specimens depict the mechanism of material removal.
Keywords: AA 6063; AISI SS304; brass; Copper; Quart; SEM; Slurry erosion

Copper-catalyzed direct arylation of indoles and related (hetero)arenes: a ligandless and solvent-free approach - Pandey, Dilip K.; Shabade, Anand B.; Punji, Benudhar (Advanced Synthesis & Catalysis, 2020)
A ligandless and solvent-free copper-catalyzed method for the regioselective C-H bond arylation of indoles and related heteroarenes is reported. The use of CuCl efficiently catalyzes the direct coupling of diverse heteroarenes with aryl iodides via chelation-assistance. This reaction could tolerate sensitive and structurally diverse functionalities, including halides, ethers, thioethers, amines, indolyl, pyrrolyl and carbazolyl groups. The directing group, 2-pyridinyl can be smoothly removed to generate C-2 arylated free-NH indoles, and the arylated indoles can further be functionalized into Tryptamine derivatives. Preliminary mechanistic study revealed a radical pathway for the arylation reaction.
Keywords: Arylation; C-H activation; Chelation-assistance; Copper; Indole; Solvent-free

Rational design of hydrophobic Cu/CuO electrodes for electrochemical oxygenation of tetralin: a strategic approach - Cherukuthota, Sri Vidya; Mathew, Elizabeth; Verma, Tushar Singh; Joshi, Krati; Selvaraj, Kaliaperumal (ChemSusChem, 2025)
Electro-organic synthesis presents a sustainable and practical alternative to traditional organic synthesis methods, which typically utilize harsh reagents and require energy-intensive conditions. Nevertheless, the challenge of achieving satisfactory conversion and selectivity rates in electrocatalytic oxidation using a non-platinum group metal (PGM) catalyst pair still needs to be addressed. This study demonstrates the application of a non-PGM-based catalyst pair for the electrocatalytic oxidation of tetralin to 1-tetralone, a highly demanded raw material in the pharma industry. Copper electrodeposited on teflonated carbon paper combined with copper foam as the electrocatalyst pair has demonstrated impressive conversion and selectivity ratios to electro-synthesize 1-tetralone at room temperature and atmospheric pressure. The optimal choice of a non-PGM catalyst, ideal mass loading, and a unique electrode configuration resulted in an ultimate conversion of about 99% of tetralin and 1-tetralone selectivity -93.7%, yield -92.6%. The reaction pathway associated with the electrochemical phenomena is supported by first principles-based density functional theory calculations and X-ray photoelectron spectroscopy of the electrocatalyst. This process has exceptional performance that can be adapted for a wide range of substrates and is straightforward, ambient, reagent-free, scalable, and therefore beneficial for industrial use. Therefore, initiatives have been taken in this direction.
Keywords: C-H activation; Copper; electrochemical oxidation; non-PGM electrocatalysts; tetralin; Tetralone